On the Impacts of Ions of Ionospheric Origin and Their Composition on Magnetospheric EMIC Waves - Lee, Justin H.; Blum, Lauren W.; Chen, Lunjin (Frontiers in Astronomy and Space Sciences, 2021)
Large numbers of theory and observation studies have been conducted on electromagnetic ion cyclotron (EMIC) waves occurring in Earth’s magnetosphere. Numerous studies have shown that accurately specifying the ions of ionospheric origin and their composition can greatly improve understanding of magnetospheric EMIC waves, specifically their generation, their properties, and their effects on the magnetospheric plasma populations. With the launch and operations of multiple recent missions carrying plasma instrumentation capable of acquiring direct measurements of multiple ion species, we use this opportunity to review recent magnetospheric EMIC wave efforts utilizing these new assets, with particular focus on the role of ions of ionospheric origin in wave generation, propagation, and interaction with particles. The review of progress leads us to a discussion of the unresolved questions to be investigated using future modeling capabilities or when new missions or instrumentation capabilities are developed.